Low risk of hepatitis B reactivation in patients with severe COVID‐19 who receive immunosuppressive therapy. Issue 1 (12th October 2020) - Rodríguez‐Tajes, Sergio; Miralpeix, Anna; Costa, Josep; López‐Suñé, Ester; Laguno, Montserrat; Pocurull, Anna; Lens, Sabela; Mariño, Zoe; Forns, Xavier
Abstract: A significant proportion of patients infected with SARS‐CoV‐2 develop severe respiratory symptoms due to an excessive immune response. Treatment of this condition may include immunosuppressive therapies, such as IL‐6 receptor antagonists and corticosteroids, which pose a risk for patients with active or past hepatitis B virus (HBV) infection. In this prospective cohort study, we analysed the risk of HBV reactivation in patients with severe COVID‐19 and resolved HBV infection undergoing immunosuppressive therapy. From 15th March to 30th April 2020, 600 patients with severe COVID‐19 were admitted to our hospital and treated with immune modulators. Data regarding HBV infection were available in 484, of whom 69 (14%) were HBsAg negative/anti‐HBc positive. For these patients, HBV reactivation prophylaxis with entecavir was strongly recommended. Complete follow‐up was available in 61 patients: 72% were male, median age was 67 years, and anti‐HBs was >10 IU/mL in 72%. The immunosuppressive drug most used was tocilizumab (72%). Despite HBV prophylaxis recommendation, 38 (62%) patients received entecavir and 23 (38%) did not. Baseline features of both groups were similar. At follow‐up, we found no cases of HBsAg seroreversion and only 2 (3%) patients (no prophylaxis group) had detectable serum HBV‐DNA (<15 IU/mL). Both were anti‐HBs negative and had normal aminotransferase levels. Our data show that the risk of HBV reactivation in patients with severe COVID‐19 and resolved HBV infection undergoing immunosuppressive treatment is low. However, if a systematic follow‐up after hospital discharge is unfeasible in patients without anti‐HBs, a short course of antiviral prophylaxis may be a safe option.